Formation of multilingual area of future competitive ability specialists in high education. (Journal of Educational Sciences, 2016)
Kazakhstan Republic has the place among the other developed countries, and has all opportunities in the sphere of education. Kazakhstan – multinational country. In Kazakhstan lives 130 ethnical groups, is developing country. Nowadays in our society two languages is changed into multi language. This multi language is given in native language, because Kazakh language is state language, Russian language is the source of science – technical news, foreign language is for human being in the sphere of world. At fi rst it is important to have specialists whoknow multi language and it helps to be multi cultural individual. According to it, the content of the article is in the sphere of educational system, to formulate multilingual area. Nowadays in the competitive society from school pupils to future specialists of high education, to labor collective specialists have to learn multilingual, it is very important to discuss this problem. On the basis of multilingual to formulate multicultural individual, and to have experiences at the level of state and in Republic is developed language centers. In conclusion, multilingual is prepared nowadays competitive ability specialist.
Keywords: future specialist; competitive ability; polylingual and polycultural; education on the basis of three languages